FINANCIAL SUSTAINABILITY OF LOCAL BUDGETS IN UKRAINE IN THE CONTEXT OF FINANCIAL INCLUSION AND POST-WAR ECONOMIC RECOVERY - KRUPKA, Mykhaylo; ZAMASLO, Olha; PETYK, Marta (Scientific journal «World of Finance», 2025)
Вступ. У сучасних умовах повномасштабної військової агресії роль місцевих бюджетів у забезпеченні фінансової безпеки держави та сталого розвитку територій суттєво зросла. Зменшення економічної активності, руйнування інфраструктури, вимушена міграція та збільшення соціальних витрат посилюють фінансові виклики для органів місцевого самоврядування. Фінансова інклюзія виступає важливою складовою зміцнення фінансової спроможності громад, проте її реалізація ускладнена обмеженим доступом до фінансових послуг, особливо у прифронтових регіонах. Мета – обґрунтувати теоретичні засади і розробити практичні рекомендації щодо зміцнення фінансової стійкості місцевих бюджетів України в умовах розширення фінансової інклюзії та забезпечення ефективного фінансування в реаліях воєнного часу й повоєнного відновлення економіки. Результати. Досліджено роль місцевих бюджетів у забезпеченні сталого розвитку територіальних громад й загальнодержавного економічного зростання. Проаналізовано структуру та динаміку доходів і витрат місцевих бюджетів, відзначено особливу роль міжбюджетних трансфертів у системі місцевих фінансів. Оцінено роль їхньої стійкості, обґрунтовано необхідність пошуку резервів власних доходів у формуванні фінансової бази органів місцевого самоврядування в умовах війни та повоєнного відновлення. За допомогою кореляційного аналізу досліджено вплив ключових макроекономічних чинників на формування дохідної бази місцевих бюджетів. Запропоновано фінансову модель забезпечення органами місцевого самоврядування соціально-економічного добробуту відповідно до цілей сталого розвитку території. Наголошено на важливості впровадження системного підходу до підвищення рівня фінансової грамотності населення та розширення фінансової інклюзії шляхом реалізації державної концепції розвитку цифрової економіки, небанківського фінансового сектору, цифровізації фінансових послуг і впровадження альтернативних механізмів фінансування з метою зміцнення фінансової спроможності місцевих бюджетів. Висновки. Результати проведеного комплексного аналізу підтверджують наявність суттєвих трансформацій у структурі доходів місцевих бюджетів України під впливом воєнного конфлікту, зокрема внаслідок перерозподілу частини податку на доходи фізичних осіб на користь державного бюджету. Визначено, що міжбюджетні трансферти залишаються ключовим інструментом забезпечення фінансової стійкості місцевих бюджетів в умовах воєнного стану. Динаміка доходів і видатків свідчить про здатність місцевих бюджетів функціонувати в умовах суттєвих обмежень та викликів, забезпечуючи виконання пріоритетних завдань, зокрема відновлення постраждалих територій і підтримку процесів повоєнної відбудови національної економіки. Introduction. In the context of full-scale military aggression, the importance of local budgets in ensuring the financial stability of the state and sustainable development of territories has increased significantly. The decline in economic activity, the destruction of infrastructure, the forced displacement of the population and the increase in social spending exacerbate the financial challenges for local governments. Financial inclusion is an important factor in strengthening the financial capacity of communities, but its implementation is complicated by limited access to financial services, especially in frontline regions. The purpose of the article is to substantiate the theoretical foundations and develop practical recommendations for strengthening the financial sustainability of local budgets in Ukraine in the context of expanding financial inclusion and ensuring effective financing in the realities of wartime and post-war economic recovery. Results. The paper examines the importance of local budgets in ensuring the sustainable development of territorial communities and national economic growth. The structure and dynamics of local budget revenues and expenditures are analyzed, focusing on the significant role of inter-budgetary transfers in the local finance system. The importance of the financial stability of local budgets is assessed and the need to intensify the search for additional sources of own income under martial law and during the post-war recovery period is substantiated. Based on the results of the correlation analysis, the influence of the main macroeconomic factors on the formation of the revenue part of local budgets is determined. A financial model is proposed that allows local governments to effectively ensure socio-economic development in accordance with the goals of sustainable development. Emphasis is placed on the feasibility of implementing a systemic approach to increasing the financial literacy of the population and expanding financial inclusion through the implementation of the state policy of digitalization of the economy, development of the non-bank financial sector, expanding access to digital financial services and introducing alternative financing mechanisms to strengthen the financial capacity of local budgets. Conclusions. According to the results of a comprehensive analysis, it was found that the military conflict led to significant transformations in the structure of revenues of local budgets of Ukraine, in particular through the redistribution of part of the personal income tax in favor of the state budget. It was determined that inter-budgetary transfers remain the main tool for ensuring the financial stability of local budgets under martial law. The study of the dynamics of revenues and expenditures confirmed the ability of local budgets to adapt to new conditions and fulfill priority tasks, in particular, to restore the affected territories and support the post-war recovery of the national economy.